Budget Policy of the New Federal Government - Überblick (Wirtschaftsdienst)
Abstract The new federal government of SPD, Bündnis 90/Die Grünen and FDP has promised a “decade of future investments” in its coalition agreement. Already in the run-up to the coalition negotiations, there were controversial discussions about the fiscal policy options and room for manoeuvre. The red lines of the new coalition partners — adherence to the debt brake, reform of basic security, no tax increases, green investments — were often seen as “squaring the circle”. The authors discuss whether the financing instruments mentioned in the coalition agreement are suitable for coping with the central fiscal challenges in the coming years and how the budgets can be brought into line with the debt brake and the fiscal rules at the EU level.